Cancer Prevention Diet: Assessment of Young Adults (20-29 Years) Knowledge, Dietary Habits and Practices - Akansha, Thota; Shaida, Bushra (Journal for Research in Applied Sciences and Biotechnology, 2022)
Promotion of a healthy lifestyle is an important part of cancer prevention. This study aimed to evaluate the knowledge, attitude and practices (KAP) of young adults towards nutrition related to cancer prevention. A cross-sectional survey was conducted among a convenience sample of 150 participants. Knowledge, attitude and practices towards diet and health were evaluated by a questionnaire with open- and closed-ended questions. Likert scale was used to analyse the questions related to attitude and practice and was classified as seldom eaten (0-1 days/week), often eaten (2–3 days/week) and always eaten (4–7 days/week). The study confined to non-medical background adults, so as they don’t have medical knowledge related to the subject. The average age of the studied population was between 18-22 years from which 45% were male students and rest were females. Students belong to different religion and cultures. Nutrition knowledge of the studied population was good almost 68.34% students know that fruits and vegetables are a good source of vitamins and minerals and it also help in boosting immunity. The scoring on Likert scale indicate that students often eat diet which is rich in antioxidants and have less knowledge regarding the cancer prevention diet. Findings suggest that nutrition and health promoting programs need to be emphasised for promoting healthy lifestyle practices which help in combatting deadly diseases like Cancer. Adults need to have a better understanding so that a better and healthy future can lead to the development of the country.